Effect of foam-mat drying on kinetics and physical properties of Japanese threadfin bream (Nemipterus japonicus) powder - A. Mohamed, Abdulrahim; Mohammad Rashedi, Ismail-Fitry; Rozzamri, Ashari; Bakar, Jamilah (John Wiley & Sons, 2022)
Japanese threadfin bream (Nemipterus japonicus) minced meat foams added with methyl cellulose (MC) at a concentration of 0.5%, 1.0%, and 1.5% w/w with foam thickness of 0.5 mm were subjected to foam-mat drying (FMD) at two drying temperatures (70 and 80°C). The objective of this study was to investigate the drying kinetics of the minced fish meat foams at different drying temperatures and MC concentrations. The effect of FMD conditions on the physical properties of powdered samples was also investigated. The drying data were fitted to a selected thin-layer drying models based on moisture ratio. The Page model was found to be the best model (R2 = 0.9930, χ2 = 0.0005 and RMSE = 0.0202) to describe the drying curves of threadfin bream foams. The L*, a*, b*, and whiteness values of FMD fish powder were significantly affected by all the factors including the interaction (p < .05). An increase in particle size from 116.22 to 131.80 μm was observed as the drying temperature and MC concentration increased. The powder showed good—fair flowability and are within the acceptable range. Both drying temperatures yielded fish powder with satisfactory physical characteristics.